Affordability of Original and Generic Antihypertensive Drugs Under the National Centralized Drug Procurement Policy and Basic Medical Insurance System: A Cross-Sectional Survey in Xi’an, China - Yamin Zou; Jing Mao; Yalin Dong; Luting Yang; Weihua Dong; Yan Hao (International Journal of Clinical Practice)
Chinese government had implemented 8 rounds of National Centralized Drug Procurement (NCDP) in mainland China from 2019 to 2023. The purpose of this study is to assess the affordability profile and variation of policy-related antihypertensive drugs in the context of NCDP, generic substitution, and basic medical insurance policy pre-NCDP (in 2018) and post-NCDP (in 2023) in Xi’an. The affordability of 34 NCDP policy-related drugs, including 17 bid-winning generic drugs (GDs) in the NCDP list and 17 originator brands (OBs) containing the same ingredients with these GDs, was analyzed and compared, respectively, by the standard survey method of World Health Organization and Health Action International (i.e., the ratio of monthly out-of-pocket expenditure to minimum daily wage standard). Under pre-NCDP policy, the monthly out-of-pocket drug cost of all OBs and 10 GDs was more than 1 day’s wage and was unaffordable. Under post-NCDP policy, the affordability of all drugs was improved dramatically; for uninsured patients, 11 OBs and only GD (lercanidipine tablets) were still unaffordable; for patients with Urban Employee Basic Medical Insurance, all of OBs and GDs were affordable, and for patients with Urban and Rural Residents Basic Medical Insurance, 7 OBs were unaffordable, and all of GDs was considered affordable. The implementation of the NCDP policy had remarkably enhanced affordability of selected drugs. GDs are more affordable than OBs. There was obvious affordability discrepancy between outpatients with different types of medical insurance in Xi’an. To enhance affordability of antihypertensive drugs, more effective and long-term measures should be implemented, such as expanding the scope of centralized purchased drugs, promoting substitution of GDs for OBs, and increasing reimbursement of outpatient drug expenses for patients with urban and rural residents’ basic medical insurance.